Legal Standing of The Deed of Sale and Purchase Against Expired Building Rights Certificate (Case Study of Decision No. 571/Pdt.G/2021/PN.Bks jo. Decision No. 591/PDT/2022/PT.BDG) - Salim, Gerardus Aldo; Gunadi, Ariawan (Devotion : Journal of Research and Community Service, 2024)
This research aims to determine, assess, and analyze the legal status of the Land Sale and Purchase Deed (AJB) compared to the Expired Building Use Rights Certificate, to investigate and analyze the role of a notary in land registration implementation and reconstruction, and to identify and analyze the latest provisions regarding land ownership rights. This research utilizes a normative juridical approach with a descriptive analytical research method. The data used in this research are the disputed land cases located in Kampung Bojong Menteng, Rawalumbu District, Bekasi City, referring to the Expired Building Use Rights Certificate based on Decision No. 571/Pdt.G/2021/PN.Bks jo Decision No. 591/PDT/2022/PT.BDG. Based on the analysis, it is discovered that Decision No. 591/PDT/2022/PT.BDG, issued on November 10, 2022, has invalidated Decision No. 571/Pdt.G/2021/PN.Bks, issued on August 8, 2022, by the Bekasi District Court. Several differences were identified, including: (1) differences regarding the disputed object; (2) differences regarding the parties involved in the dispute; and (3) differences regarding the principle of nebis in idem. These differences prove the existence of unlawful acts committed by PT. Bangun Tjipta Pratama as the owner of the Expired Building Use Rights Certificate, with unclear ownership rights over the land owned by Rekson Sitorus, and the unlawful act conducted by the Bekasi National Land Agency, which issued SHGB No. 7 as the rightful owner of the land in question.